Evaluating technology transfer and new product development in Malaysian manufacturers - Jabar, Juhaini; Soosay, Claudine (2010)
This paper is based on a larger study of Strategic Technology Alliances in the Malaysian manufacturing industry; and examines how organisational learning attributes (comprising absorptive capacity, nature and type of alliances and learning environment) affect technology transfer and new product development. Results are established through survey data from 335 organisations and analysed using structural equation modelling. Our findings establish that technology transfer is highly dependent on learning attributes and that this capability can result in innovative new product development. This study provides consideration for Malaysian manufacturers in enhancing their technological capabilities so as to sustain competitiveness and accelerating the industrialisation of the nation.